Charge separation in donor-acceptor spiro compounds at metal and metal oxide surfaces investigated by surface photovoltage - Dittrich, Th (2013)
Molecules with donor (diphenylamine) and acceptor moieties (dicyano or cyanoacrylic acid moieties) were linked by fluorene or spirobisfluorene cores and the chain length has been changed by introducing a thiophene group between fluorene and diphenylamine. Four different kinds of fluorene and spirobisfluorene compounds were adsorbed from highly diluted solutions at ultra-thin nanoporous TiO2 (np-TiO2), Au and ITO surfaces. Charge separation has been investigated by surface photovoltage spectroscopy in the fixed capacitor and Kelvin probe arrangements in vacuum. Striking differences between the interaction of linking (dicyano or cyanoacrylic moieties) and different substrates were observed. Intra-molecular charge separation and electron injection have been distinguished and the directed adsorption of spiro compounds was deduced.